Simulation-based optimization of the control strategy of variable-frequency chilled water pump in data center: A case study in Beijing. Issue 1 (June 2021) - Chong, L W; Huang, J W; Liu, Q; Zhang, Z; Chen, C; Qi, Z; Dai, N; Zhang, C; Ling, J H; Ruan, Y; Wang, Y X
Abstract: Reducing the energy consumption of air-conditioning system is one of the important means to improve the operation energy efficiency of data center, and the energy consumption of water pump accounts for a relatively high proportion of the energy consumption of air-conditioning system. This paper studied the reduction of operation energy consumption of water pump from the perspective of optimizing its control strategy. Based on the simulation model of the case system, this paper simulated the operation energy consumption of the chilled water pump when two control strategies (the constant DP control and the constant DT control of the main water supply-return pipeline) were used under different load demand. The calculation results show that both two control strategies can reduce the energy consumption of the chilled water pump compared with non-control, and the constant DT control is better. In addition, under two control strategies, the load distribution characteristics of system have an impact on the working state point and energy consumption of the chilled water pump.